Next-Generation Contraceptive Intravaginal Ring: Comparison of Etonogestrel and Ethinyl Estradiol In Vitro and In Vivo Release from 3D-Printed Intravaginal Ring and NuvaRing - Isabella C. Young; Allison L. Thorson; Mackenzie L. Cottrell; Craig Sykes; Amanda P. Schauer; Rani S. Sellers; Rima Janusziewicz; Kathleen L. Vincent; Soumya Rahima Benhabbour (MDPI AG, 2024)
Intravaginal rings (IVRs) represent a well-established, woman-controlled and sustained vaginal drug delivery system suitable for a wide range of applications. Here, we sought to investigate the differences in etonogestrel (ENG) and ethinyl estradiol (EE) release from a 3D-printed IVR utilizing continuous liquid interface production (CLIP™) (referred to as CLIPLOW for low drug loading and CLIPHIGH IVRs for high drug loading) and NuvaRing, a commercially available injection molded IVR. We conducted in vitro release studies in simulated vaginal fluid to compare the release of ENG and EE from CLIPLOW IVRs and NuvaRing. CLIPLOW IVRs had a similar hormone dose to NuvaRing and exhibited slightly slower ENG release and greater EE release in vitro compared to NuvaRing. When administered to female sheep, NuvaRing demonstrated greater ENG/EE levels in plasma, vaginal tissue and vaginal fluids compared to CLIPLOW IVR despite similar drug loadings. Leveraging observed hormones levels in sheep from NuvaRing as an effective contraceptive benchmark, we developed a long-acting CLIPHIGH IVR with increased ENG and EE doses that demonstrated systemic and local hormone levels greater than the NuvaRing for 90 days in sheep. No signs of toxicity were noted regarding general health, colposcopy, or histological analysis in sheep after CLIPHIGH IVR administration. Our results provided (1) a comparison of ENG and EE release between a 3D-printed IVR and NuvaRing in vitro and in vivo, (2) a preclinical pharmacokinetic benchmark for vaginally delivered ENG and EE and (3) the generation of a 90-day CLIP IVR that will be utilized in future work to support the development of a long-acting ENG/EE IVR combined with an antiretroviral for the prevention of HIV and unplanned pregnancy.